A Longitudinal Study of Facebook, LinkedIn, & Twitter Use - Archambault, Anne; Grudin, Jonathan (CHI 2012 Proceedings, Austin, TX, USA, 2012)
We conducted four annual comprehensive surveys of social networking at Microsoft between 2008 and 2011. We are interested in how these sites are used and whether they are considered to be useful for organizational communication and information-gathering. Our study is longitudinal and based on random sampling. Between 2008 and 2011, social networking went from being a niche activity to being very widely and heavily used. Growth in use and acceptance was not uniform, with differences based on gender, age and level (individual contributor vs. manager). Behaviors and concerns changed, with some showing signs of leveling off.